IMPLEMENTASI KEBIJAKAN PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA ZONA MERAH PADA KAWASAN ALUN-ALUN DAN MASJID RAYA KOTA BANDUNG - Cania Grenada; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2017)
Implementation of Policy Planning and Development Street Vendor in the Red Zone area Central Square of The City and the grand mosque Bandung city is regulated through the Local Government Act of Bandung City (Perda) and Regulations Mayor Area (Perwal) Number 571 Year 2014 as an amendment Regulations Mayor Area number 888 Year 2012 on implementation guidelines Organize and Development Street Vendors in Bandung, especially in the Red Zone area Central Square of The City and the grand mosque Bandung city is not in accordance with the prescribed rules. The purpose of this research is to know how the activity implementation of policy by executing the instructions, which the measurement of success seen on three things: planning activities, training, and monitoring, control and enforcement. The next purpose was to describe the supporting factors and inhibiting factor the implementation of the policy. The method used in this research is qualitative - descriptive type, with key informants from agencies involved in the Special Task Force team coaching arrangement and street vendors, street vendors, and society. Data was collected through interviews, observation, and documentation. The results showed that the implementation is already well underway in accordance with the implementation guidelines activities although the outcome has not been maximized. While inhibiting factor in the implementation of this policy were standard and policy objectives, both human and budgetary resources, and economic conditions. Advice that can be given are a feasibility study placement locations Street Vendor and they economic ability, the attention of every department in the budget, make SOP and MOU clearly, and increase the number of officers and support facilities in supervisory activities.